2018
DOI: 10.2501/jar-2018-030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Face Images and Face Pareidolia on Consumers' Responses to Print Advertising

Abstract: The present research investigates whether print advertisements featuring faces (i.e., "face ads") or face-like images (i.e., "pareidolian ads") are better able to capture consumer attention than ads that do not include such elements. In two studies, the research examined the effects of exposing consumers to print ads containing faces or pareidolian images for short time lapses (0.5, 1, and 3 seconds). The results show that both ad types capture viewers' attention and are more frequently recognized than adverti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 71 publications
1
21
0
Order By: Relevance
“…This is consistent with findings that faces capture more attention than competing visual stimuli and are processed at higher speed and in greater detail (e.g., Devue, Belopolsky and Theeuwes 2012). This attentional bias has also been demonstrated in print advertising (Guido, Pichierri and Pino 2018). From a brand perspective, facial consumer images in UGC can be a double-edged sword.…”
Section: Consumer Responses To Different Brand Image Perspectivessupporting
confidence: 87%
“…This is consistent with findings that faces capture more attention than competing visual stimuli and are processed at higher speed and in greater detail (e.g., Devue, Belopolsky and Theeuwes 2012). This attentional bias has also been demonstrated in print advertising (Guido, Pichierri and Pino 2018). From a brand perspective, facial consumer images in UGC can be a double-edged sword.…”
Section: Consumer Responses To Different Brand Image Perspectivessupporting
confidence: 87%
“…Next, we needed to edit our stimuli and properly manipulate anthropomorphism. In this procedure we drew on prior experiments that mostly used human-face features to induce anthropomorphic thinking (e.g., [63][64][65][66]). Accordingly, facial morphology (i.e., smiling or frowning eyes and mouths) works as a sufficient cue to make one attribute humanlike qualities to inanimate objects (in evolutionary terms, faces and face-like images constitute one of the strongest visual stimuli that captures attention and conveys significant information about the "humanness" of an object [67]).…”
Section: Research Design and Stimulimentioning
confidence: 99%
“…Simultaneously, such framing seems to be a strong marketing tool. [53] revealed that almost 91.7 percent of face advertisements had attracted attention more than no-face advertisements. By incorporating faces and image in advertising message, an organization may avoid the possibility of banner blindness phenomenon [54].…”
Section: B Literature Reviewmentioning
confidence: 99%